Artificial Transcription Factors for Tuneable Gene Expression in Pichia pastoris - Naseri, Gita; Prause, Kevin; Hamdo, Housam Haj; Arenz, Christoph (Frontiers in Bioengineering and Biotechnology, 2021)
The non-conventional yeast Pichia pastoris (syn. Komagataella phaffii) has become a powerful eukaryotic expression platform for biopharmaceutical and biotechnological applications on both laboratory and industrial scales. Despite the fundamental role that artificial transcription factors (ATFs) play in the orthogonal control of gene expression in synthetic biology, a limited number of ATFs are available for P. pastoris. We employed P. pastoris to characterise plant-derived ATFs developed for the Saccharomyces cerevisiae toolbox. The plant-derived ATFs contain the binding domain of TFs from the plant Arabidopsis thaliana, in combination with the activation domains of yeast GAL4 and plant EDLL and a synthetic promoter harbouring the cognate cis-regulatory motifs. Chromosomally integrated ATFs and their binding sites (ATF/BSs) resulted in a wide spectrum of inducible transcriptional outputs in P. pastoris, ranging from as low as 1- to as high as ~63-fold induction with only small growth defects. We demonstrated the application of ATF/BSs by generating P. pastoris cells that produce -carotene. Notably, the productivity of -carotene in P. pastoris was ~4.8-fold higher than that in S. cerevisiae, reaching ~70% of the -carotene productivity obtained in a S. cerevisiae strain optimised for the production of the –carotene precursor, farnesyl diphosphate, by rewiring the endogenous metabolic pathways using plant-derived ATF/BSs. Our data suggest that plant-derived regulators have a high degree of transferability from S. cerevisiae to P. pastoris. Successful tuning of protein expression levels was demonstrated not only for the reporter gene but also for -carotene production as an example application in pathway flux regulation. The plant-derived ATFs, together with their cognate binding sites, powerfully increase the repertoire of transcriptional regulatory modules for the tuning of protein expression levels required in metabolic engineering or synthetic biology in P. pastoris.